Understanding Health Risk Assessment in Female Sex Workers (FSW) and Its Relationship With the Frequency of Sexual Transactions - Rico Januar Sitorus; Lusi Rahmayani; Anita Rahmiwati; Rizma Adlia Syakurah; Danny Aerosta; Merry Natalia Panjaitan (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Female sex workers carry out sexual transactions that pose a high risk to their health. They experience a high risk of health problems, especially transmission of sexually transmitted infections. There are various factors that female sex workers (FSW) carry out sexual transactions with frequent frequency, such as poverty, gender inequality, and limited access to productive assets. This study aims to determine the associated between the frequency of sex transactions and health risks. This research uses a quantitative approach with a cross-sectional design. The population of this study was all female sexual workers (FSW), with a sample size of 162 taken by purposive sampling. The results of this study show that the majority of FSWs have had a sexual transaction frequency more than two times in the last week, amounting to 79.5%, with a prevalence of high health risks of 75.9%. Based on the multivariate test, it is known that the frequency of sexual transactions is associated with health risks after controlling for the variables age and length of time as a FSW with an Adjusted Odds Ratio of 3.467 (1.415-8.494). Health risks FSW who engage in sexual transactions more than two times have a risk of 3.467 (1.415-8.494) times experiencing high health risks compared to female sex workers who engage in sexual transactions less than two times after controlling for age and length of time as female sex workers. When carrying out work in sexual exploration, FSW should continue to use sexual protective equipment and carry out regular health checks, especially for sexually transmitted infections.